Cross-linked dry bonding: A new etch-and-rinse technique - Zhou, Jianfeng (2016)
Objective To determine if acid-etched, cross-linked dentin can be dehydrated without lowering bond strength below that of cross-linked wet-bonded dentin in vitro. Methods Using extracted human third molars, control acid-etched dentin was bonded with Single Bond Plus, using either the wet- or dry-bonding technique. Experimental acid-etched dentin was treated with 5 mass% grape seed extract (GSE) in different solvents for 1 min before undergoing wet vs dry resin-dentin bonding with Single Bond Plus. Completely demineralized dentin beams were treated with 5% GSE for 0, 1 or 10 min, before measuring stiffness by 3-point flexure. Other completely demineralized beams were treated similarly and then incubated in buffer for 1 week to measure the collagen solubilization by endogenous dentin proteases. Results 24 h microtensile bond strengths (μTBS) in wet and dry controls were 53.5 ± 3.6 and 9.4 ± 1.8 MPa, respectively (p < 0.05). 5% GSE in water gave μTBS of 53.7 ± 3.4 and 39.1 ± 9.7 MPa (p < 0.05), respectively, while 5% GSE in ethanol gave μTBS of 51.2 ± 2.3 and 35.3 ± 2.0 MPa (p < 0.05). 5% GSE in 5% EtOH/95% water gave wet and dry μTBS of 53.0 ± 2.3 and 55.7 ± 5.1 MPa (p > 0.05). Cross-linking demineralized dentin with 5% GSE increased stiffness of dentin and decreased collagen degradation (p < 0.05). Significance 5% GSE pretreatment of acid-etched dentin for 1 min permits the dentin to be completely air-dried without lowering bond strength.